Policy networks to upscale climate smart agriculture in Jamaica - Gordon, Una May (Technical Centre for Agricultural and Rural Cooperation, 2019)
Una May Gordon, Principal Director, Climate Change Division, in the Ministry of Economic Growth and Job Creation in Jamaica explains how policy networks in Jamaica are working to support projects related to Climate Change through focal points in different departments and Ministries.